Matrimonial law in Ivory Coast 1901-2012. Between legislative unification and customary resistance - (:unkn) unknown (My University, 2017)
The inefficiency of the positive law in Africa is considered as one of the underlying reasons of its underdevelopment and/or of its development malaise. The state of lawlessness that prevails in Côte d’Ivoire in marriage-related issues appears to be the case in point, being one of the most instructive and globalizing within the correlations between legal order and development in its widest sense. As a matter of fact, like in all of the former French colonies of French West Africa block, Côte d’Ivoire’s legal (at least, in a positivist sense) system is a product of its colonial past. Therefore, the legal systems in all these young African states are naturally inspired by the French law, through the channel of colonial law. However, Côte d’Ivoire’s solution differs from most of those of its fellow regional states. The new Ivorian government opted for an outright alignment of their law and the legal system with that of the former colonizer. For the civil law, this translated into the adoption of the French Code of 1804, taken for a token of development and social revolution, at the expense of countless civil customs considered to be incompatible with the new constitutional order and nation-building. Out of this political will of assimilation and legal unification - that has been ongoing in Côte d’Ivoire since independence - was born a true conflict of norms. On the one hand, a state law, especially in matrimonial matters, is prevalent but still strives to take root. On the other hand, civil customs that are still attractive bite into the credibility of the official law.
Keywords: African Research